Examining the Application of the Opening Minds Survey in the Community Health Centre Setting. (January 2018) - van der Maas, Mark; Stuart, Heather; Patten, Scott B.; Lentinello, Emily K.; Bobbili, Sireesha J.; Mann, Robert E.; Hamilton, Hayley A.; Sapag, Jamie C.; Corrigan, Patrick; Khenti, Akwatu
Objective: Stigma has been identified as a complex and problematic issue. It acts as a major barrier to accessing care and can exacerbate the experience of a health condition, particularly for clients with mental illness and substance use issues. Scales designed to assess stigmatising attitudes towards those with mental illness and substance use problems among health care providers are necessary to evaluate programs designed to reduce that stigma. The goal of this study was to evaluate the internal reliability and external validity of the Opening Minds Survey for Health Care Providers (OMS-HC). Methods: The current study examined the use of the OMS-HC in assessing stigma held by Community Health Centre (CHC) staff towards clients with mental and/or substance use problems. Participants represented staff from 6 CHCs in the Greater Toronto Area ( n = 190). Results: The OMS-HC was found to have acceptable internal reliability for the 15-item version of the scale (α = 0.766) and mixed reliability for its subscales (α = 0.792-0.673). Confirmatory factor analysis showed good absolute (root mean square error of approximation = 0.013) and relative fit (Tucker-Lewis index = 0.996) for the current data. The OMS-HC was also shown to correlate with a series of scales commonly used in stigma research. Conclusions: After testing for internal validity and comparing the OMS-HC to other commonly used scales for assessing stigma and attitudes concerning recovery, the scale was found to be appropriate for the CHC setting and may be advantageous over the use of multiple scales.